Validitas dan Realibiltas Skala General Health Questionare-12 (GHQ-12) untuk Deteksi Distres Psikologis pada Individu yang Mengalami Quarter-life Crisis di Indonesia. - Balqis, Audita Izza (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2025)
This study aims to test the validity and reliability of the General Health Questionnaire-12 (GHQ)-12) for the Indonesian version, specifically for individuals who experience a quarter-life crisis. Individuals who experience a quarter-life crisis are identical in the form of psychological distress. The development of the GHQ-12 instrument was carried out to facilitate professionals in detecting levels of psychological distress as well as as an instrument in providing appropriate treatment. 300 participants (M= 23.70; SD = 2.64) were involved in this study. The reliability of Cronbach's Alpha (α=0.903) showed GHQ-12 as an acceptable instrument. The GHQ-12 was found a one-dimensional model. CFA with goodness of-fit was found GHQ-12 was accepted, value of X2= 153.893; RMSEA=0.079; GFI=0.921; TLI= 0.918; and CFI=0.933. This study’s results indicate satisfactory validity and reliability for GHQ-12 as an instrument in detecting psychological distress for individuals experiencing a quarter-life crisis. The implications of this study can be used as a reference in providing appropriate interventions for overcoming psychological distress.